CONCEPTUAL FRAMEWORK OF ANALYSIS OF INFORMATION SECURITY MODELS OF CLOUD SYSTEMS OF THE CLASS «INFRASTRUCTURE AS A SERVICE» - E. V. Olizarovich; A. I. Brazhuk (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
A process based on the role approach for the synthesis of information security models of cloud computing systems based on applied system and threat models is described; the result is a security model, expressed, for example, in recommendations for improving information security or containing elements of the security configuration. The architecture of the system for analyzing models of information security of cloud computing systems is proposed. It includes a subsystem of analysis and modeling, a knowledge base and a subsystem of integration with external sources of knowledge. The system is model-oriented (detailed, high-level, applied, synthesized) and involves automatic processing of knowledge in the field of vulnerability management and software configuration. It is proposed an approach to solve the problem of constructing hierarchies of architectures models and threat models, realizing a combined analysis of functions and components.